PENGARUH PAJAK KENDARAAN BERMOTOR (PKB) DAN BEA BALIK NAMA KENDARAAN BERMOTOR (BBN-KB) TERHADAP PAD ACEH - Nurul Aliah; Abubakar Hamzah; Muhammad Nasir (Syiah Kuala University, 2019)
AbstractThis study aims to determine the effect of motor vehicle tax and the tariff of transfer motor vehicle name to thelocally-generated revenue, the contribution of the locally-generated revenue to the total revenue of districts in Aceh province. The data used in this research is time series during the period 2007-2013. The data analysis method used in this research is multiple linear regression with ordinary least square (OLS). The results showed that motor vehicle tax and the tariff of transfer motor vehicle name significantly had a positive effect on the locally-generated revenue of districts in Aceh province. The contribution of the locally-generated revenue to total regional revenue is relatively low, the contribution of motor vehicle tax to the locally-generated revenue is higher than the contribution of the tariff of transfer motor vehicle name to the locally-generated revenue, therefore the Aceh government should be able to improve its own regional revenue by digging up new sources of the revenue besides of motor vehicle tax and the tariff of transfer motor vehicle name. In addition and a must that is the increase of locally-generated revenue also needs to be done by improving coordination among fellow related agencies in increasing motor vehicle tax the tariff of transfer motor vehicle name.